La participation des citoyens aux choix énergétiques - Robardet, Patrick; Mockle, Daniel; Clifford, John; Bouchard, Mario (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
The authors comment on the capacity of the law to resolve problems concerning public participation in energy questions. Problems of clarity of language and consensus about objects arise in most public debates about energy. Although a particular public participation exercise may be intended to treat issues related to one policy level, questions invariably arise concerning other policy levels, be they strategic or operational. Ideally, the timing of public debate should be determined in function of the ends such debates are expected to serve, but this is difficult because of the diverse functions to be served by participation. As well, the exercise is less clear because of problems of access to and manipulation of information. Nevertheless, impartial decision-making is still perceived as leading to the best results, although the inherent limits of public participation are recognized. In the final analysis, the problems posed by public participation are not ones the law, which is contentious in orientation, can remedy.